Skyrmions and Antiskyrmions in Quasi-Two-Dimensional Magnets - Kovalev, Alexey A.; Sandhoefner, Shane (Frontiers in Physics, 2018)
A stable skyrmion, representing the smallest realizable magnetic texture, could be an ideal element for ultra-dense magnetic memories. Here, we review recent progress in the field of skyrmionics, which is concerned with studies of tiny whirls of magnetic configurations for novel memory and logic applications, with a particular emphasis on antiskyrmions. Magnetic antiskyrmions represent analogs of skyrmions with opposite topological charge. Just like skyrmions, antiskyrmions can be stabilized by the Dzyaloshinskii-Moriya interaction, as has been demonstrated in a recent experiment. Here, we emphasize differences between skyrmions and antiskyrmions, e.g., in the context of the topological Hall effect, skyrmion Hall effect, as well as nucleation and stability. Recent progress suggests that anitskyrmions can be potentially useful for many device applications. Antiskyrmions offer advantages over skyrmions as they can be driven without the Hall-like motion, offer increased stability due to dipolar interactions, and can be realized above room temperature.